Simplified Approach to Work Function Modulation in Polyelectrolyte Multilayers - Torasso, Nicolas (2017)
The layer-by-layer (LbL) method is based on sequential deposition of polycations and polyanions. Many of the properties of polyelectrolyte thin films deposited via this method depend on the nature of the topmost layer. Thus, these properties show odd-even oscillations during multilayer growth as the topmost layer alternates from polycations to polyanions. The work function of a (semi)conductive substrate modified with an LbL polyelectrolyte multilayer also displays an oscillatory behavior independent of film thickness. The topmost layer modulates the work function of a substrate buried well below the film. In agreement with previous observations, in this work, we show that the work function of a gold substrate changes periodically with the number of adsorbed layers, as different combinations of polycations and polyanions are deposited using the LbL method. For the first time, we rationalize this behavior in terms of formation of a dipole layer between the excess charge at the topmost layer and the charge of the metal substrate, and we put forward a semiquantitative model based on a continuum description of the electrostatics of the system that reproduces the experimental observations.